In vitro Antifungal Susceptibility Profile of Clinical Cladophialophora boppii in Malaysia - Tan XT; Mokhtar NN; Hassan M; Tang MM (Infection and Drug Resistance)
Xue Ting Tan,1 Nurin Nazirah Mokhtar,1 Murnihayati Hassan,1 Min Moon Tang2 1Bacteriology Unit, Infectious Diseases Research Centre, Institute for Medical Research, National Institutes of Health, Ministry of Health Malaysia, Setia Alam, Selangor, Malaysia; 2Department of Dermatology, Hospital Umum Sarawak, Ministry of Health Malaysia, Kuching, Sarawak, MalaysiaCorrespondence: Xue Ting Tan, Bacteriology Unit, Infectious Diseases Research Centre, Institute for Medical Research, National Institutes of Health, Ministry of Health Malaysia, Setia Alam, Selangor, Malaysia, Tel +60 333628968, Email tanxt@moh.gov.myPurpose: This study aimed to determine the antifungal susceptibility pattern of clinical Cladophialophora boppii isolates in Malaysia.Patients and Methods: Eight clinical strains of the C. boppii were received from various Malaysian hospitals from the year 2020 until 2024. The isolates were obtained from patients with clinical presentations suggestive of cutaneous fungal infection. Their identities were determined using microscopic, macroscopic and molecular methods, specifically internal transcribed spacer (ITS) sequencing. Next, the antifungal susceptibility of amphotericin B, itraconazole, fluconazole, voriconazole, ravuconazole, posaconazole, ketoconazole, isavuconazole, flucytosine and terbinafine against the C. boppii were determined using broth microdilution method as outlined in the Clinical and Laboratory Standards Institute (CLSI) M38 guideline. The geometric means (GM) of minimum inhibitory concentration (MIC), MIC50, and MIC90 were determined for each antifungal. Subsequently, the Kruskal–Wallis test was performed to determine the significant difference observed in the median MIC values between the different antifungal groups (azole, polyene, pyrimidine and allylamine) against the isolate. The significance value was set at p< 0.05.Results: The GM MIC, MIC50 and MIC90 of all tested antifungals except amphotericin B and fluconazole against the C. boppii were ≤ 0.25 μg/mL. In contrast, amphotericin B and fluconazole exhibited higher MICs ranging from 2 to 16 μg/mL. Furthermore, the Kruskal–Wallis test revealed a significant difference in the median MIC values across all antifungals, with a p-value of 4.94 × 10⁻5.Conclusion: In conclusion, all the C. boppii isolates in this study were susceptible to pyrimidine, allylamine, and azoles, while showing intermediate susceptibility to fluconazole and notable resistance to amphotericin B. Additionally, itraconazole and terbinafine could be recommended as the first-line therapy option, which was supported by their demonstrated efficacy (MIC ≤ 0.03 μg/mL) and clinical improvement observed in this study.Keywords: Cladophialophora boppii, fluconazole, itraconazole, terbinafine, amphotericin B, Malaysia